Enhanced Adsorption of Rose Bengal Dye from Aqueous Solution Using NaOH Activated Hydrochar Derived from Corncob Waste - R. Sivaranjanee; P. Senthil Kumar (Adsorption Science & Technology)
A potential approach to the preparation of affordable activated hydrochar is the hydrothermal carbonization of biomass wastes. In this study, hydrochar was made by hydrothermally carbonizing corncob wastes and then activating them with sodium hydroxide (NaOH). According to the findings, the adsorption capabilities of hydrochar generated at prolonged retention durations, lesser liquid-to-solid ratios, and elevated temperatures were considerably greater. The hydrochars were then analyzed utilizing a variety of characterization methods, and batch tests involving the sorption of rose bengal dye were carried out under a variety of conditions. According to the findings, activated hydrochar has a specific surface area of 12.794 m2/g. In order to better understand and characterize the process of rose bengal dye adsorption, sorption kinetics, and sorption equilibrium onto the produced hydrochars, sorption kinetics and isotherms were further examined through experimental data fitting. The NaOH-activated hydrochar’s adsorption capacity was 799.9 mg/g, respectively. The objective of this research was to assess the viability of using NaOH-activated hydrochar derived from corncobs as an economical and efficient sorbent for eliminating anionic dyes like rose bengal from aqueous solutions. Additionally, the study sought to investigate how various factors influence its sorption capabilities and to provide insights into the adsorption process through kinetic and isotherm analyses.